Simulation of Time-Varying Spatially Uniform Pressure and Near-Surface Wind Flows on Building Components and Cladding - Shen, Seraphy Y.; Masters, Forrest J.; Upjohn, Henry. L.; Sinnreich, Jon (Frontiers in Built Environment, 2017)
This paper describes a new full-scale testing apparatus for conducting performance evaluations of full-scale building envelope systems. The simulator can generate spatially uniform, time-varying pressure conditions associated with Saffir-Simpson Hurricane Wind Scale Category 5 winds while compensating for large air leakage through the specimen and also operate a high-speed wind tunnel, both with dynamic control. This paper presents system details, operating characteristics, and an early case study on the performance of large sectional door systems under wind pressure loading. Failure mechanisms are discussed, and finite element modeling is validated for two specimens. It demonstrates successful dynamic load control for large component and cladding systems, as well as simulation of flows near the building surface. These capabilities serve to complement other full-scale wind tunnel facilities by offering tools to generate ultimate load conditions on portions of the building. Further, the paper successfully demonstrates the utility of combining physical testing and computational analysis as a matter of routine, which underscores the potential of evolving full-scale testing to encompass cyber-physical approaches.